Analisis Penghambat Revitalisasi Pasar dalam Menjaga Eksistensi Pasar Tradisional - Citra Dewi Larasati; Abd. Rohman (Universitas Wijaya Kusuma Surabaya, 2023)
Competition between modern markets and traditional markets has caused traditional markets to be in a marginalized position. This has caused the Central Government to create a traditional market revitalization program, hoping that market revitalization will make traditional markets better and reduce the gap between traditional markets and modern markets. Market revitalization was also carried out by the City Government of Malang in a comprehensive and holistic manner. The City Government of Malang did not only completely overhaul the market building but also made an innovation i.e. the School of Smart Traders' People's Market (Sepasar Pedas, abbrv. in Bahasa version). The implementation of innovations involve e-retribution, Declaration of the Digital Market Pilot, and the ASN Sobo Pasar Movement. However, in carrying out several stages of the revitalization, the City Government of Malang also encountered several constrains. To obtain data regarding some of the constraints that are considered as inhibiting factors, a qualitative approach was used. Thus, the results obtained that several inhibiting factors encountered in the field by the City Government of Malang, namely: Limited Budget, Unclearness investors, Rejection of market traders, and the Problems of market management including the distribution of EDC machines that are not evenly distributed in all markets, the implementation of e-retribution is also hampered by network signals and EDC machines that often have errors.Keywords: Market Revitalization; Traditional Market